Identifying the aetiology of left ventricular hypertrophy in an athlete: importance of lifestyle modification - Ball, Miriam Jane (BMJ Publishing Group, 2009)
The aetiology of left ventricular hypertrophy (LVH) in an athlete is often difficult to identify. We describe a 29-year-old fitness instructor who was referred for investigation of syncope. He gave a history of intensive weight lifting and anabolic steroid use at supra-therapeutic doses for the preceding 6 years. Electrocardiography showed inferolateral repolarisation abnormalities and a transthoracic echocardiogram demonstrated asymmetrical LVH with reduced left ventricular cavity dimensions. There was no left ventricular outflow tract obstruction or systolic motion of the anterior mitral valve leaflet. These findings were confirmed on cardiac magnetic resonance imaging (CMR). The differential diagnosis included athlete’s heart, steroid-induced cardiomyopathy and non-obstructive hypertrophic cardiomyopathy. The patient was advised to discontinue both steroid use and intensive training. After 3 years of steroid abstinence but continued training, the syncopal episodes and the ECG abnormalities completely resolved, associated with regression of LVH on echocardiography and CMR.